Pengaruh Model Pembelajaran Kooperatif Tipe Index Card Match terhadap Hasil Belajar Matematika Siswa - Esty Saraswati Nur Hartiningrum; Ni’matus Sa’adatul Ula (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2019)
Abstract:Learning will be more meaningful if students are given the opportunity to participate in various learning activities, students can actualize their abilities inside and outside the classroom. Choosing the right learning model can create an atmosphere fun and impact on student activities and learning outcomes. The Index Card Match type cooperative learning model is to find pairs of cards that are quite fun to use to exercises about the material that has been given. The purpose of this study is to determine whether there is influence of cooperative learning model index card match type on student learning outcomes. The research method uses pre-experimental designs with one-group pretest-posttest design models. Technical analysis using hypothesis testing, namely the t-test and correlation, the requirement to do the t-test is to do a normality test. The results of data analysis showed that there was the influence of the Index Card Match type of cooperative learning model on the mathematics learning outcomes of eighth grade students of Sumobito State Junior High School 2. SPSS calculation states that the value of r count = 0.709, which is located between 0.600 <r≤0.800 which means that it is in the high criteria. Abstrak:Belajar lebih bermakna apabila siswa diberi kesempatan berpartisipasi dalam kegiatan belajar, mengaktualisasikan kemampuan mereka di dalam dan di luar kelas. Memilih model pembelajaran yang tepat dapat menciptakan suasana yang menyenangkan dan berdampak pada kegiatan siswa dan hasil belajar. Model pembelajaran kooperatif tipe Index Card Match menyenangkan digunakan untuk mengulang materi yang telah diberikan. Penelitian ini bertujuan untuk mengetahui pengaruh Index Card Match terhadap hasil belajar siswa. Metode penelitian menggunakan desain pra-eksperimental dengan model desain pretest-posttest satu kelompok. Uji hipotesis dilakukan dengan uji-t dan korelasi. Hasil analisis data diperoleh terdapat pengaruh tipe Index Card Match terhadap hasil belajar matematika siswa. Perhitungan SPSS menyatakan bahwa nilai r hitung = 0,709, yang terletak di antara 0,600 <r≤0.800 yang berarti berada dalam kriteria tinggi.